2021
DOI: 10.1017/s0950268821002661
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of risky sexual behaviour among undergraduate students at the University of Gondar, Northwest Ethiopia

Abstract: Risky sexual behavior is defined as behaviors leading to sexually transmitted diseases and unintended pregnancies. According to the Joint United Nations Program on HIV/AIDS, HIV infection was very high among adolescents and youths living in sub-Saharan Africa including Ethiopia. This study was aimed to assess the prevalence of risky sexual behavior and associated factors among undergraduate students at the University of Gondar An institution-based cross-sectional study was conducted from June to July 2019 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Furthermore, youth from rural areas had a lower likelihood of early sexual initiation compared to urban youth; this finding was consistent with previous studies [48][49][50]. This could be attributed to urban females being exposed to alcohol, substances, and pornographic materials, which leads to an early sexual debut.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, youth from rural areas had a lower likelihood of early sexual initiation compared to urban youth; this finding was consistent with previous studies [48][49][50]. This could be attributed to urban females being exposed to alcohol, substances, and pornographic materials, which leads to an early sexual debut.…”
Section: Discussionsupporting
confidence: 90%
“…This in line with a study from Ethiopia where students above the age of 24 years were found to be twice more likely to engaged in RSB as compared to younger students. 16 This finding aligns with several past cross-sectional studies that have explored the complex relationship between age and sexual behavior and observed that age may play a crucial role in influencing individuals’ likelihood of engaging in RSB. 18, 20, 24, 25 A plausible explanation for this association could be that the students of higher age may be more inclined to be involved in relationships, exhibit greater confidence in making independent decisions, and enjoy improved financial options compared to their younger students.…”
Section: Discussionsupporting
confidence: 90%
“…[11] Similar findings were shared by a studies executed among undergraduate students from Sri Lanka and from Ethiopia where 12.4% and 44.0% of the sexual active participants were practicing risky sexual behavior. [13, 14] This might be due to different characteristic of population study, study setting as well cut off point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations